2023
DOI: 10.3389/fnut.2023.1093036
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory activity of GABA-enriched Moringa oleifera leaves produced by fermentation with Lactobacillus plantarum LK-1

Abstract: IntroductionGamma-aminobutyric acid (GABA), one of the main active components in Moringa oleifera leaves, can be widely used to treat multiple diseases including inflammation.MethodsIn this study, the anti-inflammatory activity and the underlying anti-inflammatory mechanism of the GABA-enriched Moringa oleifera leaves fermentation broth (MLFB) were investigated on lipopolysaccharide (LPS)-induced RAW 264.7 cells model. The key active components changes like total flavonoids, total polyphenols and organic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This underscores the database’s commitment to encompass not only the structural and compositional aspects of compounds but also their functional and physiological attributes. This information contributes to a broader understanding of the potential health effects of compounds found in natural products such as Moringa oleifera [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the database’s commitment to encompass not only the structural and compositional aspects of compounds but also their functional and physiological attributes. This information contributes to a broader understanding of the potential health effects of compounds found in natural products such as Moringa oleifera [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ergosterol isolated from mushrooms (Auricularia polytricha, Cordyceps militaris) attenuates bisphenol A or LPS-induced BV2 microglial cell inflammation [57,58]. Zheng et al indicated that GABA-enriched Moringa oleifera leaves (MLFB) fermentation broth also could effectively alleviate LPS-induced inflammatory response by inhibiting the secretions of pro-inflammatory cytokines and the anti-inflammatory activity might be related to the relatively high contents of GABA, flavonoids, phenolics and organic acids in MLFB, its mechanism might be associated with the inhibition of TLR-4/NF-κB inflammatory signaling pathway activation [59]. Actually, treatment of EEOS-95 significantly inhibited the expression of NF-κB, iNOS, and COX-2; also enhanced upregulated of Nrf-2 and HO-1; so, we suggested that EEOS-95, an effective activator of PPAR-γ, will be an attenuated neuro-inflammation through by modulating the PPAR-γ/Nrf-2/HO-1/NF-κB signaling pathway, and ergosterol, GABA, flavonoids and polyphenol may be responsible for their activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the inhibition of NO production after treatment with CFS of the selected strains confirms their anti-inflammatory effects. Several studies have reported that GABA-producing probiotics can suppress inflammation by reducing the expression of various factors, such as NO and iNOS [23,24]. The effect of the CFS of the GABA-producing strains on iNOS protein expression in RAW 264.7 cells was analyzed using Western bloMing.…”
Section: Effect Of Cfs Of Gaba-producing Strains On Viability Of and ...mentioning
confidence: 99%